Thermodynamic aspects of ion intercalation in KhFek[Fe(CN)(6)](l)center dot mH(2)O compounds: Application to the Everit's salt/Prussian Blue transition - Gimenez-Romero, D.; Bueno, Paulo Roberto [UNESP]; Garcia-Jareno, J. J.; Gabrielli, C.; Perrot, H.; Vicente, F. (Amer Chemical Soc, 2006)
The K+ reversible processes for ion exchange in KhFek[Fe(CN)(6)](l)center dot mH(2)O host compounds (Prussian Blue) were thermodynamically analyzed. A thermodynamic approach was established and developed based on the consideration of a lattice-gas model where the electronic contribution to the chemical potential is neglected and the ion-host interaction is not considered. The occupation fraction of the intercalation process was calculated from the kinetic parameters obtained through ac-electrogravimetry in a previous paper. In this way, the mass potential transfer function introduces a new way to evaluate the thermodynamic aspect of intercalation. Finally, based on the thermodynamic approach, the energy used to put each K+ ion into the host material was calculated. The values were shown to be in good agreement with the values obtained through transient techniques, for example, cyclic voltammetry. As a result, this agreement between theory and experimental data validates the thermodynamic approach considered here, and for the first time, the thermodynamic aspects of insertion were considered for mixed valence materials.